Incidence and Risk Factors of Surgical Site Infection Following Cesarean Section at Dhulikhel Hospital - Shrestha, S; Shrestha, R; Shrestha, B; Dongol, A (Kathmandu University Medical Journal, 2015)
Background Cesarean Section (CS) is one of the most commonly performed surgical procedures in obstetrical and gynecological department. Surgical site infection (SSI) after a cesarean section increases maternal morbidity prolongs hospital stay and medical costs. Objective The aim of this study was to find out the incidence and associated risk factors of surgical site infection among cesarean section cases. Method A prospective, descriptive study was conducted at Dhulikhel Hospital, department of Obstetrics and Gynaecology from July 2013 to June 2014. Total of 648 women who underwent surgical procedure for delivery during study period were included in the study. Data was collected from patient using structred pro forma and examination of wound till discharge was done. Data was compared in terms of presence of surgical site infection and study variables. Wound was evaluated for the development of SSI on third day, and fifth post-operative day, and on the day of discharge. Results Total of 648 cases were studied. The mean age was 24±4.18. Among the studied cases 92% were literate and 8% were illiterate. Antenatal clinic was attended by 97.7%. The incidence rate of surgical site infection was 82 (12.6%). SSI was found to be common in women who had rupture of membrane before surgery (p=0.020), who underwent emergency surgery (p=0.0004), and the women who had vertical skin incision (p=0.0001) and interrupted skin suturing (p=0.0001) during surgery. Conclusion Surgical site infection following caesarean section is common. Various modifiable risk factors were observed in this study. Development of SSI is related to multi-factorial rather than one factor. Development and strict implementation of protocol by all the health care professionals could be effective to minimize and prevent the infection rate after caesarean section. Kathmandu University Medical Journal Vol.12(2) 2014: 113-116